Conspiracy Mentality Predicts Public Opposition to Foreign Trade - Jedinger, Alexander (Frontiers in Psychology, 2021)
The proliferation of protectionist sentiments and policies has raised questions about the psychological sources of trade openness among the public. The current research investigated the effects of a previously neglected factor on attitudes toward international trade: conspiracy mentality. Conspiracy mentality describes the generalized belief that political and economic events are controlled by powerful malevolent forces acting in secret. Using data from a cross-sectional survey of German adults (N = 391), I hypothesized and found that conspiracy mentality is uniquely associated with the perceived threat posed by foreign trade and opposition to international trade. These findings suggest that individual differences in conspiracy mentality make an important contribution to understanding the fears associated with economic globalization.